2005
DOI: 10.1142/s1088424605000216
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and spectroelectrochemical properties of building blocks for molecular arrays: reactions of quinoxalino[2,3-b]porphyrins containing metal(II) ions

Abstract: Quinoxalino[2,3-b]porphyrins are laterally-extended porphyrins with aromatic ring systems fused to the β,β'-positions of a pyrrolic ring of the macrocycle. They are building blocks for coplanar laterally-extended oligoporphyrins with applications in molecular electronics. The electrochemistry and spectroelectrochemistry of four such quinoxalinoporphyrins containing metal(II) ions and one free-base quinoxalinoporphyrin dissolved in nonaqueous media have been investigated and the data are compared to that seen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 19 publications
8
33
0
Order By: Relevance
“…The electrochemistry of (PTA)H 2 in non-aqueous media is similar in many respects to that which has been previously described for (PQ)H 2 under similar solution conditions [7,22]. By way of example, cyclic voltammograms for (P)H 2 , (PQ)H 2 and (PTA)H 2 in PhCN, 0.1 M TBAP are shown in Fig.…”
Section: Electrochemistry Of Mono-porphyrinssupporting
confidence: 71%
See 3 more Smart Citations
“…The electrochemistry of (PTA)H 2 in non-aqueous media is similar in many respects to that which has been previously described for (PQ)H 2 under similar solution conditions [7,22]. By way of example, cyclic voltammograms for (P)H 2 , (PQ)H 2 and (PTA)H 2 in PhCN, 0.1 M TBAP are shown in Fig.…”
Section: Electrochemistry Of Mono-porphyrinssupporting
confidence: 71%
“…It has also been shown that electron distribution in the molecule can be altered by both metalation and through chemical substitution [14]. In the current study we have extended our previous electrochemical analyses of quinoxalinoporphyrins (PQ)M [7,10,22] by the fusing of a larger ring system to a tetraazaanthracene-linked porphyrin monomer (PTA)M, and we have investigated its electronic character conjointly with its p-conjugated bis-porphyrin parent.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Their main characteristics are associated with the π-conjugated ring which imparts interesting physical and chemical properties, including the facility of stacking and yielding molecular films. The possibility of rationally manipulating their properties at the nanoscale is a relevant issue to be pursued, aiming the generation of functional molecular materials for nanotechnology devices.…”
Section: Introductionmentioning
confidence: 99%